Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.0520082514151518.a01
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene–Propylene–Diene Rubber

Abstract: EPM and EPDM are the fastest growing elastomers by virtue of their excellent ozone resistnce in comparison with commodity rubbers. Even though these rubbers have been commercially available for more than 30 years, the production and applications technologies are still very much under development. The various structural parameters of EP(D)M are described, as well as how these depend on production conditions. EP(D)M is produced in suspension with liquid propylene as dispersing agent, or most commonly in solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In both academia and industry, significant efforts have been made in achieving highly active homogeneous catalysts and stereospecific polymerization. Accordingly, numerous metallocene and postmetallocene group 4 metal catalysts have shown powerful catalytic activity and complete stereospecificity for α-olefin polymerization . In contrast, only a few examples of successful α-olefin polymerization catalyzed by group 5 metal complexes have been published. Vanadium-based heterogeneous polymerization systems first appeared in the 1950s and achieved notable success in the production of ethylene–propylene and ethylene–propylene–diene elastomers. , Vanadium precatalysts bearing chelating aryloxides have been shown by several research groups to be highly active polymerization catalysts for ethylene or ethylene–propylene . Recently, researchers reported tantalum complexes as olefin copolymerization catalysts. , For example, Fujita and co-workers synthesized tantalum complexes bearing tris­(pyrazolyl)­borate ligands (Tp) and showed that, when activated with dried methylaluminoxane (dMAO) or i Bu 3 Al/(Ph 3 C)­[B­(C 6 F 5 ) 4 ], these complexes were active ethylene polymerization catalysts that produced low- to high-molecular-weight polyethylene with relatively narrow to broad molecular-weight distributions .…”
mentioning
confidence: 99%
“…In both academia and industry, significant efforts have been made in achieving highly active homogeneous catalysts and stereospecific polymerization. Accordingly, numerous metallocene and postmetallocene group 4 metal catalysts have shown powerful catalytic activity and complete stereospecificity for α-olefin polymerization . In contrast, only a few examples of successful α-olefin polymerization catalyzed by group 5 metal complexes have been published. Vanadium-based heterogeneous polymerization systems first appeared in the 1950s and achieved notable success in the production of ethylene–propylene and ethylene–propylene–diene elastomers. , Vanadium precatalysts bearing chelating aryloxides have been shown by several research groups to be highly active polymerization catalysts for ethylene or ethylene–propylene . Recently, researchers reported tantalum complexes as olefin copolymerization catalysts. , For example, Fujita and co-workers synthesized tantalum complexes bearing tris­(pyrazolyl)­borate ligands (Tp) and showed that, when activated with dried methylaluminoxane (dMAO) or i Bu 3 Al/(Ph 3 C)­[B­(C 6 F 5 ) 4 ], these complexes were active ethylene polymerization catalysts that produced low- to high-molecular-weight polyethylene with relatively narrow to broad molecular-weight distributions .…”
mentioning
confidence: 99%
“…42 For EPDM it is well known that due to side-reactions via the unsaturated third monomers ethylidene norbornene and less so hexadiene, commonly a substantial amount of branching is obtained during polymerization, which definitely also disturbs the molecular mass distribution. 43 In addition, a distribution skewed to low molecular masses is quite common. Therefore, to investigate the influence of the molecular mass distribution, three polymers that strongly differ in their distributions were used in the present study.…”
Section: Random Network Scission Of Peroxide Vulcanized Nrmentioning
confidence: 99%